Cadangan Karbon pada “Kabun” di Kabupaten Katingan Kalimantan Tengah - Nanang Hanafi; Ise Afitah; Jariah Jariah (​Institute for Researches and Community Services Universitas Muhammadiyah Palangkaraya, 2018)
Kabun is a traditional farming system commonly practiced by people in Katingan District, Central Kalimantan. Land management carried out by the people of Katingan District since long ago using shifting cultivation. This farming system is an agroforestry system. The existence of